The impact of culture on gender stereotypes - Aimaganbetova, O. H.; Faizullina, A. K.; Adilova, E. T.; Turgumbayeva, A. M. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2017)
The article presents the results of theoretical and methodological analysis of the impact of culture on gender stereotypes. Undertaken analysis and systematization of scientific literature on the issues show that term «gender stereotypes» become extremely popular in recent years. Because the research of gender stereotypes be- comes multidisciplinary, not only branch of knowledge, but also a primes through which many important lines and dynamics of modern life can be considered, esti- mated and studied. At the level of theoretical knowledge, category «gender stereo- types» act as the most adequate mechanism, which corresponds, to adaptation to modern multicultural process. In this regard, the analysis shows that increased inter- est for research of cultural impact on gender analysis is natural.Theoretical relevance of cross-cultural approach is that it bears in itself potential possibility of creation of the unified theoretical concept that would allow integrating the conducted applied researches of influence of culture on gender stereotypes. The modern situation of cross-cultural psychology shows the existing contradiction between a large num- ber of the observations, the facts and regularities received during applied empirical and pilot studies and ability of their theoretical, conceptual judgment. The analysis shows that gender stereotypes generally stable in all cultures. In accordance with typical accepted in different cultures image of males associated as active, strong, critical, dominant, independent and expressing psychological traits as aggressive, unstable and demonstrative. From the point of view of five factor model, males as- sociated with extraversion, neuroticism and openness. Females are more passive, weak, caring and adaptive and can be characterized as submissive and guidance needed. As it can be concluded, cross-cultural research of gender stereotypes are relatively new are of cross-cultural research which can give the opportunity to deep- ly research the role of culture in creation and development of gender distinctions.